Edukasi Perilaku Hidup Bersih dan Sehat pada Anak Sekolah Masa Pandemi Covid-19 di Panti Asuhan Gotong Royong Yogyakarta - Wiwin Hindriyawati; Era Revika (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Chairman of the Central Board of the Indonesian Pediatric Association (IDAI), said that Covid-19 cases in children in the country increased by 11-12 percent. During the pandemic, the number of deaths of children under five increased by 50 percent or there were 1,000 deaths in children every week. UGM epidemiologist, said that actually from the beginning children have a risk of being infected with sars cov-2. He mentioned that in DIY itself the first case of Covid-19 was in children.(1) Clean and Healthy Living Behavior (PHBS) is needed by students at school to avoid various diseases. one of them is washing hands with soap and clean water as well as healthy snacks.(2) The purpose of this service is to provide information and education about PHBS for orphanage children, so that they are able to have PHBS. The method used begins with opening, introduction, prayer, and presentation of health education materials, question and answer sessions, evaluation, games, door prizes, closing and group photos. The results of this activity, orphanage children understand PHBS, the orphanage management is helped because children have received information and provision of PHBS during the co-19 pandemic.